The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1124/mi.8.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Ras-Induced Expression of Cytokines: A New Target of Anti-Cancer Therapeutics

Abstract: The Ras family of small guanosine triphosphatases normally transmit signals from cell surface receptors to the interior of the cell. Stimulation of cell surface receptors leads to the activation of guanine exchange factors, which, in turn, convert Ras from an inactive GDP-bound state to an active GTP-bound state. However, in one third of human cancers, RAS is mutated and remains in the constitutively active GTP-bound state. In this oncogenic state, RAS activates a constellation of signaling that is known to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 39 publications
4
69
1
Order By: Relevance
“…Several reports have shown that expression of RAS or its downstream effectors leads to the secretion of several cytokines, including TGF-β (19,30,31). However, activation of TGF-β signaling in MCF10A breast epithelial cells after RAS-G12V expression promotes increased invasion rather than senescence.…”
Section: Discussionmentioning
confidence: 97%
“…Several reports have shown that expression of RAS or its downstream effectors leads to the secretion of several cytokines, including TGF-β (19,30,31). However, activation of TGF-β signaling in MCF10A breast epithelial cells after RAS-G12V expression promotes increased invasion rather than senescence.…”
Section: Discussionmentioning
confidence: 97%
“…Production of CXCL8/IL-8 and related chemokines occurs downstream to oncogene activation [209][210][211]. Bellocq et al [170] observed a direct correlation between the number of neutrophils and IL-8 levels in broncoalveolar lavage fluids from bronchioloalveolar carcinoma patients, suggesting a role for this cytokine in neutrophil recruitment.…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
“…It was announced that the IL-8 plays role in mediating angiogenesis during tumorigenesis of human cancer. IL-8 thereby offers the potential to promote the formation of tumor (48). Based on the result of Lin et al (41), LCN2 could induce IL-8 expression and secretion and enhance cell migration and invasion.…”
Section: Acute-phase Proteins Related To Cytokinesmentioning
confidence: 99%